ON USE OF DYNAMIC PROBING IN SANDY SOILS - H. Abuel-Naga; A. Bouazza; M. Holtrigter (International Association of Lowland Technology, 2011)
The Dynamic Cone Penetration Tests (DCPT) is a rapid inexpensive field test that can be used to assess the compactness of soils. However, correlation between the results of DCPT and soil properties or any other trusted field test is not well established yet. In this paper, a General Method of Data Handling (GMDH) approach was utilized to investigate the correlation between Dynamic Probing Super Heavy (DPSH) and Standard Penetration Tests (SPTs) using test results obtained from an intensive site investigation study carried out on sandy soils in Egypt. Linking these two tests will enable DPSH to make use of well-established correlations between SPT and soil properties. The developed GMDH model indicates that the relation between the results of the two penetrometer tests is nonlinear for sandy soils and is a function of soil relative density and effective overburden pressure. The validity of the proposed correlation was verified using test results on sandy soils from different sites.